2021
DOI: 10.1155/2021/9034376
|View full text |Cite
|
Sign up to set email alerts
|

Hydromorphone Protects against CO2 Pneumoperitoneum‐Induced Lung Injury via Heme Oxygenase‐1‐Regulated Mitochondrial Dynamics

Abstract: Various pharmacological agents and protective methods have been shown to reverse pneumoperitoneum-related lung injury, but identifying the best strategy is challenging. Herein, we employed lung tissues and blood samples from C57BL/6 mice with pneumoperitoneum-induced lung injury and blood samples from patients who received laparoscopic gynecological surgery to investigate the therapeutic role of hydromorphone in pneumoperitoneum-induced lung injury along with the underlying mechanism. We found that pretreatmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 56 publications
2
6
0
Order By: Relevance
“…Hydromorphone has been reported to induce HO-1 expression levels in lung injury (16), and we speculated that Hyd may attenuate CPB-induced ALI via upregulating Nrf2/HO-1 expression levels. Thereafter, we measured Nrf2/HO-1 expression levels in rat lung tissues and disclosed that CPB treatment induced the increases in Nrf2/HO-1 expression levels and Hyd treatment further promoted the increasing trends ( P < 0.01, Fig.…”
Section: Hydromorphone Upregulates the Expression Levels Of Nrf2/ho-1mentioning
confidence: 95%
See 3 more Smart Citations
“…Hydromorphone has been reported to induce HO-1 expression levels in lung injury (16), and we speculated that Hyd may attenuate CPB-induced ALI via upregulating Nrf2/HO-1 expression levels. Thereafter, we measured Nrf2/HO-1 expression levels in rat lung tissues and disclosed that CPB treatment induced the increases in Nrf2/HO-1 expression levels and Hyd treatment further promoted the increasing trends ( P < 0.01, Fig.…”
Section: Hydromorphone Upregulates the Expression Levels Of Nrf2/ho-1mentioning
confidence: 95%
“…An existing study has reported the protective role of Hyd in CO 2 pneumoperitoneum-triggered lung injury (16), while it remains vague whether Hyd exerts the same protective role in CPB-induced ALI. To assess the impact of Hyd on lung function, we determined OI and RI in Hyd-pretreated rats after CPB induction.…”
Section: Hydromorphone Ameliorates Cpb-induced Alimentioning
confidence: 99%
See 2 more Smart Citations
“…Our previous studies have proved that HO-1 exhibits extensive protection both in LPS-stimulated RAW 264.7 cells and in a murine model of LPS-induced ALI by preserving mitochondrial dynamics through regulating fission and fusion [ 7 , 23 , 24 ]. Given the critical role of HO-1 on mitochondrial function and oxidative stress, we hypothesized that the protective effect of HO-1 might be associated with mitonuclear communication.…”
Section: Discussionmentioning
confidence: 99%